Skin tissue engineering advances in severe burns: review and therapeutic applications. Issue 1 (December 2016) - Chua, Alvin; Khoo, Yik; Tan, Bien; Tan, Kok; Foo, Chee; Chong, Si
Abstract Current advances in basic stem cell research and tissue engineering augur well for the development of improved cultured skin tissue substitutes: a class of products that is still fraught with limitations for clinical use. Although the ability to grow autologous keratinocytes in-vitro from a small skin biopsy into sheets of stratified epithelium (within 3 to 4 weeks) helped alleviate the problem of insufficient donor site for extensive burn, many burn units still have to grapple with insufficient skin allografts which are used as intermediate wound coverage after burn excision. Alternatives offered by tissue-engineered skin dermal replacements to meet emergency demand have been used fairly successfully. Despite the availability of these commercial products, they all suffer from the same problems of extremely high cost, sub-normal skin microstructure and inconsistent engraftment, especially in full thickness burns. Clinical practice for severe burn treatment has since evolved to incorporate these tissue-engineered skin substitutes, usually as an adjunct to speed up epithelization for wound closure and/or to improve quality of life by improving the functional and cosmetic results long-term. This review seeks to bring the reader through the beginnings of skin tissue engineering, the utilization of some of the key products developed for the treatment of severe burns and the hope of harnessing stem cells to improve on current practice.